Criticidade e educação filosófica: a formação humana pelo diálogo e problematização - Darcísio Natal Muraro (EccoS – Revista Científica)
This study aims to analyze the concept of criticism of Paulo Freire, emphasizing the formative role of the dialogue and the problematization. The methodology is based on bibliographic research centered on the analysis of the concept of criticism, dialogue and questioning. As a result, it is emphasizedthe understanding of criticism as incompleteness of man, questioning capacity, dialogue and democratic praxis that raises awareness, liberates, humanizes the people and transforms the world. The main aspects of criticality analyzed are related to epistemology, ethics, politics and education. These aspects of criticity are essential to a philosophical education focused on generating themes from the existential experience that contribute to significant and transformative pronunciation of the word.